2011
DOI: 10.1210/jc.2011-1563
|View full text |Cite
|
Sign up to set email alerts
|

Improved Control of Severe Hypoglycemia in Patients with Malignant Insulinomas by Peptide Receptor Radionuclide Therapy

Abstract: Radiolabeled somatostatin analog therapy can stabilize tumor growth and can be very successful in further controlling severe hypoglycemia in malignant insulinomas. In our series, this eventually resulted in improved survival outside the hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 28 publications
2
64
0
4
Order By: Relevance
“…Based on individual reports in the literature, it is known that gastrinomas respond to therapy faster, but early progression is relatively frequent [6]. PRRT treatment may improve the control of hypoglycaemia in patients with malignant insulin-secreting tumours [74,148,248,249].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Based on individual reports in the literature, it is known that gastrinomas respond to therapy faster, but early progression is relatively frequent [6]. PRRT treatment may improve the control of hypoglycaemia in patients with malignant insulin-secreting tumours [74,148,248,249].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Notwithstanding the limitations inherent in a retrospective study, including inconsistent RAI imaging methodology and timing, these findings are intriguing because poorly differentiated gastero-entero-pancreatic neuroendocrine tumors typically lose SSTR expression (14). The exception to this rule is insulinoma, in which a significant proportion of benign insulinoma (approximately one third) lack SSTR (15), whereas it is maintained in most malignant lesions, making it a suitable target for peptide receptor radionuclide therapy (PRRT) (16,17). Unlike in most gastero-entero-pancreatic neuroendocrine tumors, a prior immunohistochemical study in thyroid malignancy demonstrated predominant expression of SSTR-5 rather than SSTR-2 (18), favoring radioligands with affinity for SSTR-5 (e.g., 68 Ga-DOTA-NOC or 68 Ga-DOTATOC) over SSTR-2 ligands (e.g., 68 Ga-DOTA-TATE) in this disease.…”
Section: See Page 1512mentioning
confidence: 99%
“…However, as opposed to benign insulinomas, malignant insulinomas often lack GLP1R (60). Conversely, malignant insulinomas often do express sst 2 , which can be targeted using SRS (24,60,61,62,63,64,65,66). In various studies, GLP1R scintigraphy using 111 In-DOTAexendin-4 successfully detected benign insulinomas (60,67,68,69,70).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%